Respuesta :

Answer:

 w = -48

Step-by-step explanation:

Step one:

Simplify w/8

6 - ( 0 - w/8) = 0

Step two:

Subtracting a fraction from a whole

Rewrite the whole as a fraction using  8  as the denominator:

6 = 6/1 = 6 times 8 over 8

Equation at the end of step  2:

w + 48/8 = 0

Step three:

When a fraction equals 0

its numerator, the part which is above the fraction line, must equal zero.

Get rid of the denominator.

w+48/8 x 8 = 0 x 8

8 cancels out the denominator

Your left with: w+48=0

Solve.

w+48=0

Subtract 48 from both sides of the equation

w = -48

You are left with

w = 48